3D hierarchical porous expanded perlite-based composite phase-change material with superior latent heat storage capability for thermal management. (2nd January 2023) - Zhao, Xiaoguang; Tang, Yili; Xie, Weimin; Li, Daokui; Zuo, Xiaochao; Yang, Huaming
Highlights: A facile route was introduced to synthesize 3D hierarchical porous expanded perlite (EPP). The P/EPP FSPCM with high enthalpy and long-term cyclic stability was achieved. The mechanism of preventing paraffin leakage by EPP was analyzed by in-situ FTIR. The P/EPP panel exhibits excellent thermal management and good flame retardant. Abstract: The use of latent heat thermal energy storage (LHTES) technology is regarded as an effective strategy for smart heat management and building energy conservation. However, phase-change materials (PCMs), which are key components in LHTES systems, suffer from serious leakage in the solid-liquid phase-change process. In this work, 3D hierarchical porous expanded perlite (EPP)-based composite form-stable phase-change materials (FSPCMs) were successfully designed and constructed. The introduction of polyvinyl alcohol (PVA) was applied to regulate the porous framework of expanded perlite (EP) and endow the EPP with a superior ability to adsorb paraffin and inhibit its leakage. The final EPP-based composite FSPCM was obtained by impregnating paraffin into the EPP. This novel composite FSPCM exhibits excellent thermal properties and long-term cycling stability. The phase-change enthalpy of the composite FSPCM reaches up to 174.6 ± 2.20 J/g and remains at a high level even after 500 heating-cooling cycles. The mechanism by which EPP effectively inhibited paraffin leakage is attributed to the capillary action and surface tension of the hierarchical porous structure, and the electrostatic attraction between PVA and paraffin molecules. Most importantly, a novel panel fabricated by the optimal EPP-based composite FSPCM presents excellent thermal management performance and flame-retardant ability. The panel developed in this work shows great potential for building energy conservation.